The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/00050060500243434
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary profiles of clinical and health psychologists in Australia

Abstract: Clinical and health psychologists are, collectively, the most numerous of the professional subgroups represented by the Colleges of the Australian Psychological Society. The value of these professionals to the continued health and well‐being of the Australian society is important and this value is underscored by the commitment shown by Australian clinical and health psychologists both to intake‐level education and to the maintenance of continuing professional development once entry into the profession has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Of concern when looking across the age range of participants, is the marked reduction in male psychologists that have entered the workforce in the last 10-15 years, with the proportion of psychologists that are female being higher in the younger age groups. This finding is consistent with that of Byrne and Davenport (2005) who reported a trend towards more and younger female practitioners in their sample of clinical and health psychologists when compared to earlier demographic data. Strategies for attracting males into the psychology profession need to be considered.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Of concern when looking across the age range of participants, is the marked reduction in male psychologists that have entered the workforce in the last 10-15 years, with the proportion of psychologists that are female being higher in the younger age groups. This finding is consistent with that of Byrne and Davenport (2005) who reported a trend towards more and younger female practitioners in their sample of clinical and health psychologists when compared to earlier demographic data. Strategies for attracting males into the psychology profession need to be considered.…”
Section: Discussionsupporting
confidence: 90%
“…A study by Byrne and Davenport (2005) explored the profiles of psychologists including training, employment status, employment setting and role. However, the data were limited as the researchers sampled only those psychologists who were members of the APS College of Clinical or Health Psychologists.…”
Section: Introductionmentioning
confidence: 99%
“…Some support for this hypothesis is found in a previous study (Dienst & Armstrong, 1988) that indicated somewhat closer correlations between assessments by supervisors of similar rather than dissimilar theoretical orientations. Although most of our supervisors in the present study (as rated by the placement coordinator) espouse a cognitive behavioural orientation in line with national trends (Byrne & Davenport, 2005), and poor supervisor agreement was found for items unrelated to therapeutic orientation, the impact of differing therapeutic orientations may have influenced results on some items (e.g., 7, 8 and 9).…”
Section: Predictive Value Of Supervisor Ratingsmentioning
confidence: 49%
“…Anecdotally there has been concern for some time that psychologists are moving away from public sector work in favour of work in independent practice. This was confirmed in a study by Byrne and Davenport (2005) who looked at the role of clinical and health psychologists in Australia and found reduced participation in public sector work when compared to earlier research. Similarly, international research indicates a reduction across time of psychologists working in public sector settings such as hospitals and community health centres and an increase in the percentage of psychologists working in independent private practice (Norcross, Karpiak, & Santoro, 2005).…”
Section: Introductionmentioning
confidence: 60%